1990
DOI: 10.1111/j.1439-0329.1990.tb01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhizoctonia solani, a potentially dangerous pathogen of khasi pine and hardwoods in forest nurseries in India

Abstract: The paper describes top flaggine of Pinus kesiya and leaf web blight of 24 broad-leaved tree species caused by Rhizoctonia solani Khun anamorph of Thanatephorus cucumeris (Frank) Donk in forest nurseries in India. Damage to the foliage resulting in premature defoliation at the peak of growing season is highlighted. Infection, epidemiology and disease management are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Harsh et al (1989) briefly reported for foliage diseases caused by 14 fungal pathogens in the nurseries of Madhya Pradesh. Mehrotra (1990) described about foliar diseases caused by R. solani in forest nurseries. Maji et al (2012), observed that mulberry varieties were affected with foliar diseases viz powdery mildew, leaf rust, Myrothecium leaf spot, and Pseudocercospora leaf spot.…”
Section: Isolation and Identification Of Fungusmentioning
confidence: 99%
“…Harsh et al (1989) briefly reported for foliage diseases caused by 14 fungal pathogens in the nurseries of Madhya Pradesh. Mehrotra (1990) described about foliar diseases caused by R. solani in forest nurseries. Maji et al (2012), observed that mulberry varieties were affected with foliar diseases viz powdery mildew, leaf rust, Myrothecium leaf spot, and Pseudocercospora leaf spot.…”
Section: Isolation and Identification Of Fungusmentioning
confidence: 99%
“…The infection is seen in seedlings and proves to be fatal in most cases. Damping-off is the most common seedling problem caused by the fungus that leads to death of the seedlings (Mehrotra, 1990). Rhizoctonia damage may occur at any time during the growing season, but it is more severe on young seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…& Ravenel., Fusarium solani (Mart.) Sacc., Macrophomina phaseolina (Tassi) Goid., Phyllosticta spp., Rhizoctonia solani J. G. Kühn (Hodges, 1962;Hansen vd., 1979;Augspurger, 1990;Mehrotra, 1990;Wardlaw ve Philips, 1990;Soni vd., 1992;Viljoen vd., 1992;Sandlin ve Ferin, 1993;Viljoen vd., 1994;Chin, 1995;James vd., 1995;Khan vd., 1995;Barbey, 1996;Cellerino, 1996;Freire, 1996;Mirabolfathy ve Ershad, 1996;Motta vd., 1996;Belisario vd., 1997;Lilja vd., 1997Lilja vd., , 2007aLilja vd., , 2007bJung vd., 2005;2007;2009;Akıllı vd., 2010;Weiland vd., 2013;Aday Kaya, 2014).…”
Section: Introductionmentioning
confidence: 99%